Composición química, actividad cicatrizante y toxicidad del latex de Croton lechleri. - Cevallos Verdesoto, Diego Omar (2016)
The dermal healing activity and acute toxicity of Croton lechlerilatex were evaluated using Wistar rats. The observation period to determine the healing activity was 7 days (d) and 14 d for the toxicity. Samples for histological evaluations were prepared 7 d after incised wound. The identification of chemical compounds present in the latex was performed by using gas chromatography coupled to mass spectroscopy. From histopathological analyses, in general, wounds of untreated rats and treated with the commercial cream showed withgranulomatous inflammations,while the skins of rats treated with the latex of C. lechleriexhibited signs of repair. From evaluation of acute dermal toxicity, latex did not cause deaths or signs of toxicity in animals, at doses of 2000 mg/kg, body weight of the rats consistently increased, and no significant differences in mass balances (g/d) were observed between the groups of male and female rats, until the time of treatment with the latex.